2023
DOI: 10.3390/md21060353
|View full text |Cite
|
Sign up to set email alerts
|

State of Innovation in Alginate-Based Materials

Abstract: This review article presents past and current alginate-based materials in each application, showing the widest range of alginate’s usage and development in the past and in recent years. The first segment emphasizes the unique characteristics of alginates and their origin. The second segment sets alginates according to their application based on their features and limitations. Alginate is a polysaccharide and generally occurs as water-soluble sodium alginate. It constitutes hydrophilic and anionic polysaccharid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 204 publications
0
4
0
Order By: Relevance
“…We first analyzed the composition of PURP extract and found that it contained polysaccharides, monosaccharides and proteins (Figure 1A‐D and Figure S1). Barrier repair has been reported in this species, and monosaccharides also have repair and anti‐inflammatory effects 39,47–55 . Here, PURP promoted skin barrier repair, particularly involving members of the claudin family (Figure 2–6, 7I,K, Figure S2a and b).…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…We first analyzed the composition of PURP extract and found that it contained polysaccharides, monosaccharides and proteins (Figure 1A‐D and Figure S1). Barrier repair has been reported in this species, and monosaccharides also have repair and anti‐inflammatory effects 39,47–55 . Here, PURP promoted skin barrier repair, particularly involving members of the claudin family (Figure 2–6, 7I,K, Figure S2a and b).…”
Section: Discussionmentioning
confidence: 56%
“…Barrier repair has been reported in this species, and monosaccharides also have repair and anti-inflammatory effects. 39,[47][48][49][50][51][52][53][54][55] Here, PURP promoted skin barrier repair, particularly involving members of the claudin family (Figure 2-6, 7I,K, Figure S2a and b). We also detected the expression of other genes related to the skin barrier.…”
Section: Discussionmentioning
confidence: 99%
“…Polysaccharides can be easily modified, and this quality improves operational properties of polymer materials and expands their application areas. Sodium alginate (Alg), a widely used anionic polysaccharide, finds numerous applications in biomedicine for drug delivery [7][8][9], the food industry for packaging [10][11][12][13][14], tissue engineering to accelerate wound healing and cell transplantation [7,8,[15][16][17][18], cosmetics as water-retaining agents [19][20][21][22], etc.…”
Section: Introductionmentioning
confidence: 99%
“…Sodium alginate, a FDA-approved polysaccharide [ 4 ], is frequently used in the formulation of novel dosage forms due to its excellent biodegradability, biocompatibility, and water solubility features. As shown by Bhosale et al (contribution 3), when sodium alginate is applied to mucoadhesive chitosan nanoparticles, there is an increase in voriconazole loading capacity and in the ability of these nanoparticles to penetrate mucosa.…”
mentioning
confidence: 99%